STUDY OF FLUORIDE-INDUCED HAEMATOLOGICAL ALTERATIONS AND LIVER OXIDATIVE STRESS IN RATS - Djouadi, Anfal; Derouiche, Samir (WORLD JOURNAL OF PHARMACY AND PHARMACEUTICAL SCIENCES, 2017)
Fluorine is a necessary biological trace element for human health. However, fluoride accumulation leads to cascading effects resulting in altered physiological functions in human being. The current studies evaluated the effect of fluoride induced hematological alterations and oxidative stress in the liver of experimental rats. For this purpose, adult female Wistar albino rats divided into control and NaF treated group. sodium Fluoride (400 mg/kg b.w) added in their drinking water for 70 days. Compared with the control, a significant decrease in the body weight gain (p<0.001) and increase in relative liver weight (p<0.001) were noticed in the NaF group Our results showed that fluoride treatment caused a increase in Granulocyte (p < 0.001), White blood cell (p < 0.001), Lymphocyte (p < 0.01) and Platelets (p < 0.01) compared with the control. In addition, it led to an increases in triglyceride (p<0.001), cholesterol (p<0.01) level, GOT (p<0.01) and GPT (p<0.001) activities in serum animal compared to the control group . In contrast fluoride caused an oxidative stress by decrease in GSH level and GST activity and increase in MDA concentration compared with the control group. In Conclusion, Results demonstrated the toxic effect of high-dose of fluoride by causing oxidative stress and inflammation in hepatic tissue.
Article
Keywords: Sodium Fluoride ; liver; hematological parameters; stress oxidative.